Onco-neural antibodies and tumour type determine survival and neurological symptoms in paraneoplastic neurological syndromes with Hu or CV2/CRMP5 antibodies. Issue 4 (17th October 2008) - Honnorat, J; Cartalat-Carel, S; Ricard, D; Camdessanche, J Ph; Carpentier, A F; Rogemond, V; Chapuis, F; Aguera, M; Decullier, E; Duchemin, A M; Graus, F; Antoine, J C
Abstract : Objective: Anti-Hu antibodies (Hu-Ab) and anti-CV2/CRMP5 antibodies (CV2/CRMP5-Ab) have been identified in association with paraneoplastic neurological disorders. However, it is not clear whether these antibodies are associated with specific neurological symptoms or are only markers of anti-cancer immune reaction. Methods: To address this question, 37 patients with CV2/CRMP5-Ab and 324 patients with Hu-Ab were compared. Results: Whereas the age and sex ratio were the same between the two groups, the distribution of neurological symptoms was not. Patients with CV2/CRMP5-Ab presented more frequently cerebellar ataxia, chorea, uveo/retinal symptoms and myasthenic syndrome (Lambert–Eaton myasthenic syndrome LEMS or myasthenia gravis). They also had a better Rankin score. In contrast, dysautonomia, brainstem encephalitis and peripheral neuropathy were more frequent in patients with Hu-Ab. Limbic encephalitis occurred similarly in both groups. Small-cell lung cancer was the most frequently associated tumour in both groups of patients, while malignant thymoma was observed only in patients with CV2/CRMP5-Ab. In particular, patients with CV2/CRMP5-Ab and thymoma developed myasthenic syndrome more frequently, while patients with SCLC developed neuropathies more frequently. Chorea and myasthenic syndrome were only seen in patients with CV2/CRMP5-Ab. The median survival time was significantly longer in patients with CV2/CRMP5-Ab, and this effect was not dependent on the type of tumour. Interpretation: The data demonstrate that in patients with paraneoplastic neurological syndromes, the neurological symptoms and survival vary with both the type of associated onco-neural antibody and the type of tumour.